Memory updating and hypnotherapy in the modulation of lactose intolerance: A multiple case report (Research, Society and Development, 2025)
Lactose intolerance affects millions of people worldwide, significantly impacting quality of life due to undesirable gastrointestinal symptoms. Conventional treatments, such as dietary restriction and enzyme supplementation, fail to address potential emotional and psychological factors influencing the condition’s manifestation. This study aims to investigate the application of memory regression and updating using the RB7 method in treating lactose intolerance, analyzing whether psychological intervention can modulate patients' physiological responses. A total of 42 participants with a confirmed diagnosis were selected, of whom 36 completed the protocol. The intervention consisted of four individual hypnotherapy sessions focused on identifying and reinterpreting memories associated with adverse responses to lactose consumption. Symptom assessments were conducted before and after the intervention, as well as at a six-month follow-up. Results demonstrated a significant reduction in symptom frequency and intensity, with sustained therapeutic effects over time. These findings suggest that memory updating may play a crucial role in the physiological response to food intolerance, offering new insights for integrative therapeutic approaches. Further research is needed to elucidate the underlying mechanisms and explore its applicability to other gastrointestinal and psychosomatic conditions.